Exhibiting urban anxieties associated with spatial inequalities in Davao City through short horror films - Gonzales, Alec Gabrielle P. (2023)
Horror films have been a medium to display the urban anxieties experienced by the people in their present context. While this is true, there are no exhibitions of anxieties caused by spatial inequalities within the city center through any production works as it has been mostly a comparison of rural and urban settlements. With practice-led research, this study produced short horror films in adherence to the narratives of the residents of Davao City. Even though the city established a promising image as the metropolis of Mindanao, various concerns are being raised by residents. To concentrate on the inequalities caused by space, this study focuses on the anxieties of higher education institution learners. With that, the most common places that the participants visited are mapped to easily visualize how the city is being designed and how they are navigating the city. It has been assessed that each congressional district ? District 1, District 2, and District 3 ? in the city has unequal advantages when it comes to commercial, institutional, and leisure opportunities. On top of that, from the perspective of college students, the urban planning of Davao is adding emotional, mental, and physical exhaustion due to the challenging accessibility of their necessities and the taxing transportation system. These anxieties and elements are displayed in the produced three short horror films. These films are then screened for Davaoen?os and other audiences to realize the horrors of the spatial inequalities which are consequences of urbanization.